A study of library software systems in academic libraries in Metro Manila - Cornago, Pia Charmaine F.; Pascua-Cruz, Ma. Divina A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2003)
This study made use of the three library software systems (Athena, Follett and MaeLisa) to determine whether additional training of librarians on their applications could improve the software systems' performance. The descriptive method was used with a survey questionnaire as the main-gathering tool. Data from the websites of the software vendors supplemented the responses of one hundred twenty (120) professional librarians, eleven (11) head librarians and eleven (11) system administrators, or a total of one hundred forty-two (142) respondents of the survey. They are from eleven (11) colleges and universities that were provided by the three software systems' distributors.
The frequencies of the different responses were tabulated, the percentages of their mean scores were obtained, and the results presented as pie graphs to facilitate the analysis of data. The software packages were found to be "user-friendly". For all software systems, no user find it "very hard" working with them but rather, the majority finds it "easy" working with the software packages. Similarly for all software packages, a significant number of users find it "very easy"" working with the systems. Furthermore, the software packages were found to satisfy the primary purpose of automation because they "make work very much easy" according to majority of the respondents. Accordingly, this study confirmed that the software packages are useful for the simple reason that they "make work very much easy".
The divergence of perceptions among the users on the quality of training given by the library software vendors could be rooted on the variable computer expertise of the respondents. The lack of "resourcefulness" among the Follett users and "inadequate" training provided by its vendor apparently resulted to the response of "harder to learn" for the majority of Follett users. On the other hand, their users perceive Athena and MaeLisa as "easier to learn" because they subscribe to self-sponsored trainings in knowing more about the software packages. This could imply that computer expertise, and consequently, more efficient use of the software packages, is primarily both an inclination and an initiative. Other implications regarding interactions between librarians and software systems could be drawn from this study.
The correlation of training needs with performance of the software package was analyzed using Pearson's Correlation Coefficient r. A direct (linear) relationship was inferred for the following most used modules: OPAC, Circulation, Media Services References, CD-ROM, and Indexes. This is taken to signify that the most used modules are where both training and improvement are needed. This confirms the hypothesis that additional training of librarians would improve system performance, particularly for the most used modules. For improved overall performance of the software packages, the respondents suggested management sponsored-trainings for librarians on applications of the software packages and software vendor assistance on these trainings.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Computer software